Novel Likely Pathogenic Variants Identified by Panel-Based Exome Sequencing in Congenital Cataract Patients - Doudou Chen; Tao Yang; Siquan Zhu (Journal of Ophthalmology)
Purpose. To identify likely pathogenic variants in three families with congenital cataracts via panel-based exome sequencing. Methods. A panel containing 153 genes associated with congenital cataracts was designed. Genes were selected through reference to databases including the Human Gene Mutation Database (HGMD), Online Mendelian Inheritance in Man (OMIM), Genetic Home Reference, and the latest peer-reviewed publications on the genetics of hereditary cataracts. Panel-based exome sequencing was performed with the Illumina HiSeq X-Ten platform, and then the identified variants were confirmed with Sanger sequencing and evaluated according to the American College of Medical Genetics and Genomics (ACMG) criteria. Results. Three likely pathogenic variants were found. A novel CRYBB2: c.230G > T p.G77V variant was identified in family A, a novel CRYBB2: c.230G > A p.G77D variant was identified in family B, and a novel CRYGD: c.475delG p.A159Pfs∗9 variant was identified in family C. Conclusion. Panel-based exome sequencing revealed three likely pathogenic variants in three unrelated Chinese families with congenital cataracts. These data expand the genetic spectrum associated with congenital cataracts.